2021
DOI: 10.3389/fpsyg.2021.673829
|View full text |Cite
|
Sign up to set email alerts
|

“Three Steps Above Heaven? Really? That’s All Tactic!” New Alternative Masculinities Dismantling Dominant Traditional Masculinity’s Strategies

Abstract: Research on preventive socialization of gender violence has contributed abundant empirical evidence that attraction to violence is common among adolescents. This has meant that “bad guys,” or those who reflect the Dominant Traditional Masculinity (DTM) model, are chiefly perceived as appealing, while “good guys” are perceived as good friends but not desirable. The mainstream media tends to reproduce this traditional model of affective-sexual relationships, which has harmful effects on young girls concerning ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
0
14
0
1
Order By: Relevance
“…In this regard, the role of boys in preventing adolescent dating violence has been emphasized in community-based intervention programs to improve adolescents’ health and wellbeing [ 23 ]. Other studies have differentiated between three different types of masculinity to understand the role of men in gender violence: dominant traditional masculinities (DTM), oppressed traditional masculinities (OTM), and new alternative masculinities (NAM) [ 24 , 25 , 26 , 27 ]. DTM represent inegalitarian, dominant, and violent attitudes of men that can lead to gender violence, but that at the same time are associated with attractiveness in the dominant coercive discourse socially transmitted.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the role of boys in preventing adolescent dating violence has been emphasized in community-based intervention programs to improve adolescents’ health and wellbeing [ 23 ]. Other studies have differentiated between three different types of masculinity to understand the role of men in gender violence: dominant traditional masculinities (DTM), oppressed traditional masculinities (OTM), and new alternative masculinities (NAM) [ 24 , 25 , 26 , 27 ]. DTM represent inegalitarian, dominant, and violent attitudes of men that can lead to gender violence, but that at the same time are associated with attractiveness in the dominant coercive discourse socially transmitted.…”
Section: Introductionmentioning
confidence: 99%
“…We can state that based on the data collected we can identify that Bond increases his ethical behavior in line with a more inclusive society, however we cannot state -based on the data collected -that he also increases his attractiveness proportionally. The role of the coercive discourse (Racionero-Plaza et al, 2022;Ruiz-Eugenio, Racionero-Plaza, et al, 2020), which fosters attraction to violence (Gómez, MCS -Masculinities and Social Change, 11(2) 117 2015;Valls et al, 2008), towards non-egalitarian masculinities (Castro & Mara, 2014;Flecha et al, 2013;Rodrigues-Mello et al, 2021), in making some people see the last Bond as less attractive would be the subject of future research. How the socialization of people in this coercive discourse mediated to a lesser or greater extent in their perception of a more or less attractive Bond due to having more ethical behaviors remains to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies analyze in depth how media promote attraction to violence through a coercive dominant discourse (Puigvert et al, 2019;Puigvert & Flecha, 2018;Racionero-Plaza et al, 2020;Torras-Gómez et al, 2019;Villarejo et al, 2020) which links sexuality and violence (Rodrigues-Mello et al, 2021;Villarejo et al, 2020). The research conducted in 2010 by Neuendorf and colleagues (Neuendorf et al, 2010) evaluating 195 female characters in 20 James Bond's films concluded that sexual activity with women has increased at the same time than harm towards them has.…”
mentioning
confidence: 99%
“…Among those discourses, scientific research has found the CDD, which imposes the link between attraction and violence by portraying individuals and relationships with violent attitudes as attractive, fun and exciting R (Gómez, 2015;. Conveyed through different forms of entertainment (movies, shows, music…) and peer interactions, while the CDD presents violent masculinity models as the only attractive and desirable option, egalitarian models are deemed as convenient but lacking attractiveness and excitement (Gómez, 2015;Rodrigues-Mello et al, 2021;Villarejo et al, 2020;Villarejo-Carballido et al, 2022). In this way, the CDD leads to a double-standard frame of mind in which pleasure, fun, excitement and passion are separated from love, care, stability and egalitarianism (Gómez, 2015;Joanpere et al, 2021;Rios-González et al, 2018;Ruiz-Eugenio et al, 2021).…”
Section: State Of the Artmentioning
confidence: 99%